Electrical Impedance Dermography Differentiates Squamous Cell Carcinoma In Situ from Inflamed Seborrheic Keratoses - Elaine Wen-Ying Wong; Sarbesh Pandeya; Henry Crandall; Tristan Smart; Madisen Dixon; Kenneth M. Boucher; Scott R. Florell; Douglas Grossman; Benjamin Sanchez (Elsevier, 2023)
There are no currently available low-cost, noninvasive methods for discerning the depth of squamous cell carcinoma (SCC) invasion or distinguishing SCC from its benign mimics, such as inflamed seborrheic keratosis (SK). We studied 35 subjects with subsequently confirmed SCC or SK. Subjects underwent electrical impedance dermography measurements at six frequencies to assess the electrical properties of the lesion. Averaged greatest intrasession reproducibility values were 0.630 for invasive SCC at 128 kHz, 0.444 for SCC in situ at 16 kHz, and 0.460 for SK at 128 kHz. Electrical impedance dermography modeling revealed significant differences between SCC and inflamed SK in normal skin (P < 0.001) and also between invasive SCC and SCC in situ (P < 0.001), invasive SCC and inflamed SK (P < 0.001), and SCC in situ and inflamed SK (P < 0.001). A diagnostic algorithm classified SCC in situ from inflamed SK with an accuracy of 0.958, a sensitivity of 94.6%, and a specificity of 96.9%; it also classified SCC in situ from normal skin with an accuracy of 0.796, a sensitivity of 90.2%, and a specificity of 51.2%. This study provides preliminary data and a methodology that can be used in future studies to further advance the value of electrical impedance dermography and inform biopsy decision making in patients with lesions suspicious of SCC.